Emotivity matters for mood licensing - Lena Baunaz; Joanna Blochowiak; Cristina Grisot (Isogloss)
French distinguishes between indicative vs. subjunctive markings morphologically, by showing mood on the embedded verb. Embedded subjunctive appears with specific (classes of) matrix predicates, like vouloir (want), while the indicative mood is found with others, such as dire (say). This suggests that the subjunctive is licensed lexically by specific classes of predicates. However, the existence of verbs like rêver (dream), which seem to accept both moods, poses a challenge to this idea and raises the question of the source of optional mood selection. A recent approach sheds light on the importance of emotive contexts in the selection of subjunctive mood cross-linguistically (Baunaz & Pusks 2022, Baunaz & Lander 2024). Our hypothesis is that in cases where mood selection is optional (i.e., with alternating verbs), the subjunctive mood is licensed by the presence of the [Emo] feature, which is activated in emotive contexts. Consequently, we predict for alternating verbs, that the emotive contexts will favor the subjunctive mood, whereas the non-emotive contexts will favor the indicative mood. In contrast, the context manipulation will not affect the mood selection patterns of verbs that exclusively select either the indicative or subjunctive mood. We provide an experimental confirmation of this claim.